Synergistic immobilization of ions in mixed tin-lead and all-perovskite tandem solar cells - Yuhui Liu; Tianshu Ma; Changlei Wang; Zhenhai Yang; Yue Zhao; Zhanghao Wu; Chen Chen; Yining Bao; Yuhang Zhai; Tianci Jia; Cong Chen; Dewei Zhao; et al. (Nature Communications)
Abstract Low-bandgap (LBG) mixed tin-lead (Sn−Pb) perovskite solar cells (PSCs) suffer from inferior performance due to their high defect density. Conventionally, ethylenediammonium diiodide (EDADI) is used as a surface passivator to reduce defects and improve device photovoltaic performance, but it introduces severe hysteresis caused by excessive mobilized ions at the top interface. Here, we report a mobile ion suppressing strategy of using hydrazine monohydrochloride (HM) as a bulk passivator to anchor the free ions in LBG perovskites. The protonated hydrazine (N2H5 +) of HM formed hydrogen bonds with iodine (I–) ions, while the chloride (Cl–) ions occupied the I– vacancies, collectively impeding the migration of I– and thus mitigating the ion movement-induced hysteresis that arose from EDADI usage. The synergistic strategy of HM doping and EDADI post-treatment significantly suppresses the oxidation of Sn2+, decreases trap density, and inhibits rapid crystallization of perovskite. Consequently, we achieved a champion efficiency of 23.21% for LBG PSCs. Integrating these cells with wide-bandgap PSCs into all-perovskite tandem solar cells yields a high efficiency of 28.55% (certified 28.31%) with negligible hysteresis.